Cerebellar vermian epidermoid tumor: a report of 2 cases (2018)
BACKGROUND: Epidermoid tumors are rare, benign slow-growing congenital tumors, most frequently located in the cerebellopontine angle of the intracranial cavity. They usually grow to a large size before patients become symptomatic. Although these tumors are amenable to surgery, their adherence to neurovascular structures poses a surgical challenge that results in subtotal resection, thus increasing the risk of recurrence. CASE DESCRIPTION: We report 2 adult patients whose imaging studies revealed epidermoid tumors located in the cerebellar vermis, an uncommon site for such tumors. The patients presented with variable symptomatology. We highlight the imaging features and challenges of surgery. Both patients had good outcomes, with resolution of symptoms and neurologic deficits. CONCLUSIONS: A safe complete excision of epidermoid tumor and its capsule is possible with a good understanding of their clinical and radiologic features and a high index of suspicion. To the best of our knowledge, this is the first report of cerebellar vermian epidermoid tumors from sub-Saharan Africa.